Respuesta :

Answer:

[tex]\begin{array}{ccc}{} & {g(x) = f(x) - 2} & {g(x) = f(x) + 2} & {f(x) = 3x^2 + 3} & {g(x) =3x^2 + 1} & {g(x) =3x^2 + 5} & {f(x) = 3x^2 - 3} & {g(x) =3x^2 -5} & {g(x) =3x^2 - 1} \ \end{array}[/tex]

Step-by-step explanation:

Given

See attachment for complete question

Required

Complete the cells

For cell 1:

[tex]f(x) = 3x^2 + 3[/tex]

Solve for [tex]g(x) = f(x) - 2[/tex]

Substitute [tex]f(x) = 3x^2 + 3[/tex]

[tex]g(x) = 3x^2 + 3 - 2[/tex]

[tex]g(x) = 3x^2 + 1[/tex]

For cell 2:

[tex]f(x) = 3x^2 + 3[/tex]

Solve for [tex]g(x) = f(x) + 2[/tex]

Substitute [tex]f(x) = 3x^2 + 3[/tex]

[tex]g(x) = 3x^2 + 3 + 2[/tex]

[tex]g(x) = 3x^2 + 5[/tex]

For cell 3:

[tex]f(x) = 3x^2 - 3[/tex]

Solve for [tex]g(x) = f(x) - 2[/tex]

Substitute [tex]f(x) = 3x^2 - 3[/tex]

[tex]g(x) = 3x^2 - 3 - 2[/tex]

[tex]g(x) = 3x^2 - 5[/tex]

For cell 4:

[tex]f(x) = 3x^2 - 3[/tex]

Solve for [tex]g(x) = f(x) + 2[/tex]

Substitute [tex]f(x) = 3x^2 - 3[/tex]

[tex]g(x) = 3x^2 - 3 + 2[/tex]

[tex]g(x) = 3x^2 - 1[/tex]

So, the complete cell is:

[tex]\begin{array}{ccc}{} & {g(x) = f(x) - 2} & {g(x) = f(x) + 2} & {f(x) = 3x^2 + 3} & {g(x) =3x^2 + 1} & {g(x) =3x^2 + 5} & {f(x) = 3x^2 - 3} & {g(x) =3x^2 -5} & {g(x) =3x^2 - 1} \ \end{array}[/tex]

Ver imagen MrRoyal